2019
DOI: 10.1186/s13031-019-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder and depression among Syrian refugees residing in the Kurdistan region of Iraq

Abstract: BackgroundSince the Syrian civil war began in March 2011, more than half of the Syrian population was forced to escape from their homes, and more than 5 million of them fled their country. The aim of the present study is to estimate the psychological consequences of this conflict among the refugee population who fled to Iraq.MethodIn 2017, a team of locally trained psychologists and social workers interviewed 494 married couples (988 individuals) who were Syrian Kurdish refugees in the Kurdistan Region of Iraq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
88
4
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 64 publications
(100 reference statements)
23
88
4
7
Order By: Relevance
“…Vonnahme, Lankau, Ao, Shetty, & Cardozo (2016) in their study among Bhutanese Refugees in the United States, found inability to read and write a host country's language increased the odds of symptoms of depression four times compared to those who could read. Moreover, daily stressors such as living in unsafe places, lack of access to basic needs, absence of social support and living conditions in the host country contributed to higher levels of depression among Rohingya adult refugees who were semi or illiterate in Bangladesh (28). These results are in line with the Diathesis-Stress Model of Robert P.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Vonnahme, Lankau, Ao, Shetty, & Cardozo (2016) in their study among Bhutanese Refugees in the United States, found inability to read and write a host country's language increased the odds of symptoms of depression four times compared to those who could read. Moreover, daily stressors such as living in unsafe places, lack of access to basic needs, absence of social support and living conditions in the host country contributed to higher levels of depression among Rohingya adult refugees who were semi or illiterate in Bangladesh (28). These results are in line with the Diathesis-Stress Model of Robert P.…”
Section: Discussionsupporting
confidence: 73%
“…Close et al, (2016) reported higher depression prevalence of 43% among Iraqi refugees, 41% of depression was also reported among Karenni refugees residing along the Burmese-Thai border (27). A study done among Syrian refugees living in Iraq reported 80% prevalence of depression (28). Studies conducted among refugees in Uganda and Southern Sudan identified high prevalence of depression at 67.4% and 49.9%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 24 participants refused to be enrolled despite their initial consent when initiating the survey. The study included 1951 responders with 527 (27.0%) being males, and 1538 (78.8%) participants being within the age range of (19)(20)(21)(22)(23)(24)(25) Table 2, there were signi cantly higher K10 scores in participants who changed places of living multiple times due to war, females, participants with low SES, low educational levels, younger age groups, and participants who were distressed from war noise. When regressing the previous variables from Table 2 on K10 scores by using forward linear regression, they were all signi cant (P<0.05) and R 2 was 1.6%, 1.0%, 1.1%, 0.6%, 0.2%, and 0.2%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In primary care, around 25% of patients scored 20 or over (17,18). In Iraq, around 60% of Syrian refugees had probable depression (25). Another study found that 56% of the Syrian refugees at Alzatary Camp in Jordan suffered from mental distress, and 46% believed they needed mental support (26).…”
Section: Discussionmentioning
confidence: 99%